An Integrated Representation of Linguistic and Social Functions of Code-Switching - Hartmann, Silvana; Choudhury, Monojit; Bali, Kalika (Proceedings of LREC 2018, 2018)
We present an integrated representation of code-switching (CS) functions, i.e., a representation that includes various CS phenomena (intra-/inter-sentential) and modalities (written/spoken), and aims to derive CS functions from local and global properties of the code-switched discourse. By applying it to several English/Hindi CS datasets, we show that our model contributes (i) to the standardization and re-use of CS data collections by creating a resource footprint, and (ii) to the study of CS functions by creating a systematic description and hierarchy of reported functions together with the (local and social) properties that may affect them. At the same time, the model provides a flexible framework to add emerging functions, supporting theoretical studies as well as the automatic detection of CS functions.